Women’s and men’s experiences with participative decision-making at workplace and organizational levels - Plückelmann, Clara; Gustafsson Sendén, Marie; Bernhard-Oettel, Claudia; Leineweber, Constanze; Sczesny, Sabine (Frontiers in Psychology, 2024)
Introduction The concept of participative decision-making (PDM) has been well established as a positive organizational factor, and has recently gained attention as a measure of gender inclusivity in the workplace. However, findings regarding gender differences in the experiences of PDM are inconclusive. This study hypothesized that women perceive themselves as less influential than men at the organizational level rather than at the workplace level. Furthermore, the study explored whether these assumed gender differences depend on the gender typicality of occupational positions and professions. We expected gender differences to be more pronounced for male-typed positions and professions (e.g., leadership, engineer) compared to non-male-typed occupational positions and professions (e.g., non-leadership, nurse). Methods Data on experiences with participative decision-making at the workplace and organizational levels were drawn from a large representative Swedish survey (N = 10,500; 60% women). Results Results showed that women experienced being less influential than men at the organizational level, whereas the experiences of women and men did not differ at the workplace level. The gender difference at the organizational level was not related to the gender typicality of position and profession. Discussion The findings highlight the importance of the inclusion of both women and men in strategic, large-scale decisions for achieving gender equality at work.